The Effects of Perceived Organizational Support on Innovative Performance of High School Football Players: The Mediating Role of Self-Management - Eunah Hong; Yejee Jeong (Korea Institute of Sport Science, 2021)
PURPOSE The purpose of this study was to investigate the effects of perceived organizational support of high school football players on innovative performance. Of particular note, we focused on examining the mediation effect of self-management between perceived organizational support and innovative performance. METHODS A total of surveys returned was 137 and the data used for the final analysis was 130. The data was processed using SPSS 21.0 statistical program and Lisrel 9.2 for confirmatory factor analysis. RESULTS The results of the analysis were as follows: first, perceived organizational support of high school football players had a positive effect on players' self-management. Second, players' self-management had a positive effect on players' innovative performance. Third, players' self-management fully mediated between perceived organizational support and players' innovative performance. CONCLUSIONS The study concluded that maximizing both perceived organizational support and self-management of the high school football players are necessary in order for the organization to achieve high level of innovative performance.